French film music scoring in the thirties: a stylistic tripartition. Issue 3 (1st October 2020) - Rossi, Jérôme
ABSTRACT: The novelty of talking cinema in the thirties, supported by an artisanal production system that allowed some individual initiatives to be expressed, produced a ferment of ideas in the field of French music scoring as evidenced in the writing of many composers. If Hollywood cinema quickly opted for ubiquitous narrative music, the author will show that French productions were much more varied by focusing on three non-exclusive approaches represented by Arthur Honegger, Alexis Roland-Manuel and Vincent Scotto. The first advocates for an 'autonomist' approach where music accompanies the images while also retaining its own structural logic (rondo, fugue, leitmotifs). The second develops a 'song-writing' approach in his collaborations with Marcel Pagnol and beyond: diegetic and extra-diegetic songs with short melodies both with and without lyrics (chorus and stanza form, sequential form). The third, finally, favours a more cinematographic conception by detaching himself from pre-conceived forms and composing music that complements the noises and the voices on the soundtrack.